The Implementation of the Aceh Special Autonomy Policy towards Poverty Alleviation in Aceh - Safaruddin, Safaruddin; Subhilhar, Subhilhar; Humaizi, Humaizi; Kusmanto, Heri; Hasan, Effendi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The outcome of the Helsinki MoU peace agreement between the Central Government and the Free Aceh Movement on August 15, 2005, was the granting of special autonomy funds to Aceh Province. This funding aims to improve Aceh’s welfare and development. However, in reality, the allocated special autonomy funds have not been able to resolve various issues in Aceh, particularly in reducing poverty levels. The present study aimed to analyze the factors contributing to the limited impact of special autonomy funds on poverty alleviation in Aceh. Utilizing a descriptive qualitative approach, this study involved the collection of primary and secondary data. The asymmetric decentralization theory guided the analysis of this phenomenon. The findings reveal that the special autonomy funds allocated to Aceh Province by the central government have demonstrated a limited impact on poverty alleviation within the region. This can be attributed to several key factors: the absence of a grand design master plan, formalized through a Qanun, for the general allocation fund by the Aceh government; the lack of prioritization of poverty alleviation within the special autonomy budget allocation; and the issue of misappropriation of special autonomy funds in Aceh (corruption).